Leonard Garment papers - Garment, Leonard; Garment, Leonard
Correspondence, memoranda, reports, notes, appointment books, press releases, printed material, and other papers relating chiefly to Garment's service as a legal advisor to presidents Richard M. Nixon and Gerald R. Ford. Files from Garment's White House years include material on the Watergate Affair, Indian relations, Jewish issues, Legal Services Corporation, presidential campaigns, and school integration. Papers documenting Garment's subsequent practice of law in Washington, D.C., include material on the Bank of Credit and Commerce Interntional (BCCI), INSLAW (firm), the Jonathan Jay Pollard espionage case, tension in the Middle East. and Robert C. McFarlane, whom Garment represented in the Iran-Contra investigations. Also includes working papers for Garment's book, Crazy Rhythm (1997), and other writings.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Lawyer and government official; born 1924.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ford, Gerald R., -- 1913-2006.; McFarlane, Robert C; Nixon, Richard M. -- 1913-1994.; Pollard, Jonathan Jay, -- 1954-; Bank of Credit and Commerce International; INSLAW (Firm); Legal Services Corporation; Espionage -- United States; Indians of North America -- Government relations -- 1934-; Iran-Contra Affair, 1985-1990.; Jews -- United States; Practice of law -- Washington (D.C.); Presidents -- United States -- Election; School integration; Watergate Affair, 1972-1974.; Middle East -- Politics and government -- 1945-1979.; United States -- Politics and government -- 1969-1974.; United States -- Politics and government -- 1974-1977.; Lawyers; Public officials